Story and Emotion A Study in Affective Narratology - Per Thomas Andersen (Scandinavian University Press (Universitetsforlaget), 2016)
Per Thomas Andersen analyzes literary works by Kierkegaard, Dostoyevsky, Ibsen, Hamsun, J.P. Jacobsen, Schoenberg and Knausgaard. Based on perspectives from literary studies, philosophy, cognitive psychology, neurobiology and media studies, professor Andersen analyzes characters in the novels, temporal and spatial aspects of the narratives, sources of emotional impulses, and different ways in which the streams of affects turn out to be as important as events in the narrative style of the chosen authors. Per Thomas Andersen is professor of Scandinavian Literature at the University of Oslo.